Key Problems and Solutions Research on Interworking Between Mobile Network and WLAN - Lei Cao; Bo Wang; Bin Dong; Zhen Shao; Xiao Shen (Dianxin kexue)
With the explosive growth of the mobile internet applications，coordination between mobile networks and WLAN is playing an important role in telecom operators’ smart pipe development. The feasibility of 3GPP-WLAN interworking structures with consideration of the capability of existing networks and UE，were studied. A feasible structure based on the 3GPP SaMOG standard was also proposed，with corresponding solutions to the key issues in its implementation.